1996
DOI: 10.1111/j.1525-1470.1996.tb01414.x
|View full text |Cite
|
Sign up to set email alerts
|

Keratitis, Ichthyosis, and Deafness (KID Syndrome): Review of the Literature and Proposal of a New Terminology

Abstract: The so‐called KID (keratitis, ichthyosis, deafness) syndrome is a congenital disorder of ectoderm that affects not only the epidermis, but also other ectodermal tissues such as the corneal epithelium and the inner ear. Sixty‐one patients who fulfill the criteria for this syndrome were identified in a review of the literature through December 1993. All had cutaneous and auditory abnormalities, and 95% also had ophthalmologic defects. The most frequent clinical features were neurosensory deafness 90%, erythroker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
93
1
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(98 citation statements)
references
References 46 publications
2
93
1
2
Order By: Relevance
“…The lesions often appear in the form of wart-like or hyperkeratotic plaques of erythrokeratodermia, located symmetrically on the scalp, face, and skin folds. 3 The presence of generalized xerosis, keratosis pilaris and hypohidrosis is common. In 79% of cases there may be diffuse alopecia of the scalp as well as atrichia and partial loss of lateral ends of the eyebrows.…”
Section: Discussionmentioning
confidence: 99%
“…The lesions often appear in the form of wart-like or hyperkeratotic plaques of erythrokeratodermia, located symmetrically on the scalp, face, and skin folds. 3 The presence of generalized xerosis, keratosis pilaris and hypohidrosis is common. In 79% of cases there may be diffuse alopecia of the scalp as well as atrichia and partial loss of lateral ends of the eyebrows.…”
Section: Discussionmentioning
confidence: 99%
“…As manifestações oculares da síndrome KID ocorrem geralmente na infância, após o surgimento das alterações cutâneas e auditivas. Portanto, o acrônimo KID pode não estar completo nas fases precoces da doença (7) . O mecanismo da doença corneana não parece ser inflamatório, como implica o termo "ceratite", mas resultante de um distúrbio ectodérmico generalizado, com atrofia ou ausência das glândulas de Meibomius, queratinização dos ductos das glândulas lacrimais e deficiência de células basais limbares.…”
Section: Discussionunclassified
“…In a classic review, [17] 61 patients who met the criteria for this syndrome were identified. All had cutaneous and auditory abnormalities, and 95% of them also had ophthalmologic defects.…”
Section: Other Genodermatosis With Hypotrichosis Kid Syndrome (Keratimentioning
confidence: 99%